Diversity of Ants (Hymenoptera: Formicidae) on Several Types of Plantations in Dharmasraya Regency, West Sumatra Province - Silvia Roza; Yaherwandi; Siska Efendi (Faculty of Agriculture, Tompotika Luwuk University, 2022)
Ant diversity in the plantation ecosystem has an important role in maintaining the balance of the ecosystem and the continuity of crop production. It aims to find out ant diversity and the role of ants present in oil palm, rubber, and cocoa plantation ecosystems in Dharmasraya District. The research location is Kecamatan Pulau Punjung, Sitiung, and Koto Besar. The method used in this research is Systematic Random Sampling (Random Design Selected). Sampling using the Qudran Protocol method is Soil And Leaf Litter Sieving, Pitfall trap, Bait Trap, and Hand Collecting. Identification is done at the Laboratory of Animal Taxonomy, Biology Department, Faculty of Mathematics and Natural Sciences, Andalas University. The diversity and evenness of ants in some types of plantations in Dharmasraya Regency were moderate (H '<1) and (E <0.63). There were 16 species of ants; the most abundant species were Aneplolephis graciliphes and Odontoponera denticulate.